Tinjauan Hukum Ekonomi Syari’ah Terhadap Realisasi Akad Dana Tabarru Di Ajb Bumiputra Syari’ah 1912 Cabang Subang - Adawiyah, Endah Robiatul; Wazin, Wazin; Afifah, Divia Nurul; Setiadi, Rudi; Sumarna, Agus (UIN Sultan Maulana Hasanuddin Banten, 2021)
Abstract This research aims to explain how sharia insurance mechanism works, the application of Akad Tabarru' in AJB Bumiputera 1912 Syari'ah Subang Branch, Tabarru' Fund Management at AJB Bumiputera Syari'ah 1912 Subang Branch and Sharia Economic Law Review on The Realization of Tabarru' Fund Agreement at AJB Bumiputera Syari'ah 1912 Subang Branch, The approach used is descriptive analytical qualitative research, the results obtained show, there are two forms of contracts in premiums paid i.e. for investment and for tabarru , tabarru agreement in implementation in the provision of alms funds from premiums collected between fellow customers by the company, sharia principles used is a takaful principle (please help) and implemented by mutually bear in the implementation of tabarru agreement, in sharia insurance, there is no such thing as mutual risk transfer from participants to the company, because in practice contributions (premiums) paid by participants will not occur transfer of hund , the ownership status of the funds remains attached to the participants as sahib al-mal. Sharing of risk among fellow participants is realized through the mechanism of tabarru agreement, tabarru account is used as a full source of funds for the payment of claims in sharia insurance, which means that the fund account helps each other from all participants, which from the beginning has been sincerely intended by the participants for the needs of their siblings Kata Kunci: Hukum Ekonomi Syariah, Akad Tabarru’ Abstrak Penelitian ini bertujuan untuk menjelaskan bagaimana mekanisme Kerja Asuransi Syariah, Penerapan Akad Tabarru’ di AJB Bumiputera 1912 Syari’ah Cabang Subang, Pengelolaan Dana Tabarru’ di AJB Bumiputera Syari’ah 1912 Cabang Subang dan Tinjauan Hukum Ekonomi Syariah Terhadap Realisasi Akad Dana Tabarru’ di AJB Bumiputera Syari’ah 1912 Cabang Subang, Pendekatan yang digunakan adalah penelitian kualitatif deskriptif analitis, hasil yang diperoleh menunjukan, terdapat dua bentuk akad dalam premi yang dibayarkan yakni untuk investasi dan untuk tabarru, akad tabarru di impelemntasikan dalam pemberian dana sedekah dari premi yang dikumpulkan antar sesama nasabah oleh perusahaan, prinsip-prinsip syari’ah yang diggunakan adalah prinsip takaful (tolong menolong) dan diimplementasikan dengan cara saling menanggung dalam implementasi akad tabarru, dalam asuransi syariah, tidak ada yang namanya saling transfer resiko dari peserta ke perusahaan, karena dalam praktek kontribusinya (premi) yang dibayarkan oleh peserta tidak akan terjadi transfer of hund, status kepemilikan dana tersebut tetap melekat pada peserta sebagai sahib al-mal. Sharing of risk diantara sesama peserta diwujudkan melalui mekanisme akad tabarru, rekening tabarru’ dijadikan sumber dana sepenuhnya untuk pembayaran klaim dalam asuransi syari’ah, rekening dana saling tolong menolong kepada sesama dari seluruh peserta, yang sejak awal sudah diniatkan dengan ikhlas oleh peserta untuk keperluan saudara-saudaranya Kata Kunci: Hukum Ekonomi Syariah, Akad Tabarru’